2013
DOI: 10.1016/j.bcp.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Destruxins: Fungal-derived cyclohexadepsipeptides with multifaceted anticancer and antiangiogenic activities

Abstract: Destruxins (Dtx) are secondary metabolites of the entomopathogenic fungus Metarhizium anisopliae. Recently, Dtx came into focus of interest as anticancer therapeutics. However, data on human and especially on cancer cells are fragmentary. In order to successfully establish novel anticancer therapeutics, a broad knowledge on the cellular and molecular mechanisms underlying their activity is essential. Consequently, this study aimed to investigate the impact of the most common Dtx derivatives A, B and E on human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 39 publications
4
43
0
1
Order By: Relevance
“…The activity of DB against cancer cells have been suggested or studied on murine leukemia, epidermal carcinoma, non-Hodgkin lymphoma, and non-small cell lung cancer cells [7-9,11,12]. We also report that DB has potential as a new therapeutic agent against human colorectal cancer and non-small cell lung cancer [10,13].…”
Section: Discussionmentioning
confidence: 87%
“…The activity of DB against cancer cells have been suggested or studied on murine leukemia, epidermal carcinoma, non-Hodgkin lymphoma, and non-small cell lung cancer cells [7-9,11,12]. We also report that DB has potential as a new therapeutic agent against human colorectal cancer and non-small cell lung cancer [10,13].…”
Section: Discussionmentioning
confidence: 87%
“…Destruxins (Dtx) A, B, and E from the entomopathogenic fungus Metarhizium anisopliae presented strong antiproliferative activity against HCT116 colon cancer cells. The molecular mechanism investigation indicated that the cytotoxicity of three Dtx derivatives depends on intrinsic apoptosis induction and associated with phosphoinositide‐3‐kinase (PI3K)/Akt pathway . Beauvericin as a well‐known mycotoxin exerted antiproliferative activity against H4IIE hepatoma cells via the induction of apoptosis that was accompanied by an inhibition of NF‐ k B‐activity and modulation of MAP‐kinases .…”
Section: Resultsmentioning
confidence: 99%
“…anisopliae, Clavicipitaceae) [9][10][11], which plays an important role as a biological control agent [12,13]. It is widely accepted that dtxs exhibit a wide variety of biological activities [12,[14][15][16][17][18], although they are best known for their insecticidal and phytotoxic activities [12,15]. However, there are concerns that the use of Metarhizium spp.…”
mentioning
confidence: 99%